2002
DOI: 10.1556/aphyt.37.2002.4.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soybean Mosaic Virus on the Activity of Carbohydrases in Leaves of Sensitive and Resistant Soybean Plants

Abstract: Influence of soybean mosaic virus (SMV) on activity of 1,3-β-D-glucanase, α-D-mannosidase, β-D-galactosidase and β-D-glucosidase in leaves of extremely resistant (cv. Devamusume) and sensitive (cv. Primorskaya 529) young soybean plants was studied. Enzymes can be put in order of increase of their activities as follows: β-D-glucosidase, β-D-galactosidase, α-D-mannosidase and 1,3-β-D-glucanase independently of a cultivar.High level of 1,3-β-D-glucanase activity was detected in leaves of the healthy resistant pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The strong isolate of PVX caused more severe damage to plants (systems necrosis) with a greater increase in the content of PR‐proteins during all 3 weeks of the experiment than the weak and medium ones. Earlier we (Andreeva et al., 2002) reported that the soya bean mosaic virus did not influence the activity of 1,3‐ β ‐ d ‐glucanase in extremely resistant soya bean plants (cv. Dewamusume) but increased the activity of this enzyme in sensitive plants (cv.…”
Section: Discussionmentioning
confidence: 92%
“…The strong isolate of PVX caused more severe damage to plants (systems necrosis) with a greater increase in the content of PR‐proteins during all 3 weeks of the experiment than the weak and medium ones. Earlier we (Andreeva et al., 2002) reported that the soya bean mosaic virus did not influence the activity of 1,3‐ β ‐ d ‐glucanase in extremely resistant soya bean plants (cv. Dewamusume) but increased the activity of this enzyme in sensitive plants (cv.…”
Section: Discussionmentioning
confidence: 92%